Bodily relations and reciprocity in the art of Sonia Khurana. (November 2017) - Wainwright, Leon
This article explores the significance of the 'somatic' and 'ontological turn' in locating the radical politics articulated in the contemporary performance, installation, video and digital art practices of New Delhi-based artist, Sonia Khurana (b. 1968). Since the late 1990s, Khurana has fashioned a range of artworks that require new sorts of reciprocal and embodied relations with their viewers. While this line of art practice suggests the need for a primarily philosophical mode of inquiry into an art of the body, such affective relations need to be historicised also in relation to a discursive field of 'difference' and public expectations about the artist's ethnic, gendered and national identity. Thus, this intimate, visceral and emotional field of inter- and intra-action is a novel contribution to recent transdisciplinary perspectives on the gendered, social and sentient body that in turn prompts a wider debate on the ethics of cultural commentary and art historiography.